TRANSABDOMINAL ULTRASONOGRAPHY LUMBAR SPINE: METHODOLOGY, NORMAL ANATOMY - Пономаренко С. О. (World of Medicine and Biology, 2015)
The methodology of transabdominal ultrasound examination of the lumbar spine is described. This methodology has the advantage of the possibility of standardizing the research by determining the precise anatomical landmarks, standard projections and scan modes. Ultrasonography defined regulatory parameters intervertebral discs, spinal canal, radicular channels, ligaments measured at the level of the intervertebral disc and blood flow in the veins of the epidural lumbar spine.